Amorphous tailing-based cadmium-arsenic synchronous adsorption material as well as preparation method and application thereof
By destroying the crystal structure of tailings and loading nano zero-valent metals on its surface, the problem of insufficient repair capacity for cadmium and arsenic composite contaminated soil in the prior art is solved, and efficient adsorption and magnetic recovery of cadmium and arsenic are achieved.
Patent Information
- Application Number
- CN202411920904.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-04-18
AI Technical Summary
The prior art is difficult to effectively repair cadmium and arsenic composite contaminated soil, especially due to the high crystallinity and negative surface charge of silicate minerals in tailings, the adsorption capacity to cadmium and arsenic is limited.
By mixing the tailings with alkali metal and calcining at high temperature, the crystal structure is destroyed to form amorphous tailings. The nano-zero-valent metal is then loaded in situ on its surface, improving its adsorption capacity to cadmium and arsenic.
The synchronous and efficient adsorption of cadmium and arsenic is achieved, and the activity of tailings and the binding ability to arsenic is improved. The prepared composite material has high-efficiency adsorption performance and good magnetic recovery characteristics.
Smart Images

Figure BDA0005207960450000121 
Figure BDA0005207960450000131 
Figure HDA0005207960460000011
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of soil heavy metal pollution control and solid waste pollution control, and specifically relates to an amorphous tailings-based cadmium and arsenic simultaneous adsorption material and a preparation method and application thereof. Background Art
[0002] As a key driver of global economic development, the mining industry plays an important role in providing raw materials needed for industry. However, the development of this industry is also accompanied by environmental challenges, especially heavy metal pollution of soil around mining areas, such as soil cadmium and arsenic pollution, which has become an environmental problem that needs to be solved urgently. Long-term ingestion of crops from cadmium and arsenic contaminated soil may cause a variety of health problems. At the same time, due to the cumulative effect of toxicity, cadmium and arsenic compound contaminated soils usually show higher biological toxicity and are more harmful. Therefore, it is urgent to take effective measures to repair cadmium and arsenic compound contaminated soils to alleviate the pollution problems left over from mining activities.
[0003] The opposite geochemical behaviors of cadmium and arsenic greatly increase the difficulty of remediation of cadmium-arsenic co-contaminated soil. A possible solution is to use suitable adsorbent materials to simultaneously fix cadmium and arsenic. Silicate materials are widely used due to their advantages such as good porosity, surface charge, and cation exchange capacity. Tailings waste generated during mining, such as molybdenum tailings, iron tailings, copper tailings, and gold tailings, are recognized as high-silicon resources. These accumulated tailings not only occupy precious land resources, but may also cause environmental pollution, dam breaches, landslides, collapses and other risks. The development of adsorbent materials using the above-mentioned tailings as raw materials provides a potential feasible strategy for the remediation of cadmium-arsenic contaminated soil and the safe treatment and effective utilization of tailings. However, the current preparation of cadmium-arsenic co-fixation materials using tailings as raw materials mainly faces the following two problems: first, the silicon in the tailings mainly exists in high-crystallinity minerals such as quartz and mica, which have stable structures, low activity, and very limited binding capacity for Cd; second, the common property of silicate materials, namely the inherent negative charge on their surfaces, results in them having almost no binding capacity for metal ions such as arsenic that exist in neutral or anionic states.
[0004] Therefore, in order to achieve the simultaneous and efficient fixation of cadmium and arsenic, it is meaningful to improve the activity of tailings and their ability to bind arsenic. Summary of the invention
[0005] In order to solve the shortcomings and deficiencies of the prior art, the primary purpose of the present invention is to provide a method for preparing an amorphous tailings-based cadmium and arsenic simultaneous adsorption material.
[0006] The preparation method of the present invention first mixes the tailings with alkali metals and calcines them in a muffle furnace. After the calcined product is fully washed and dried, the solid product obtained is an amorphous tailing with a destroyed mineral crystal structure. The amorphous tailings are mixed with a metal ion solution, and a nano zero-valent metal is in situ loaded on its surface through a reduction reaction of a reducing agent such as sodium borohydride to obtain an amorphous tailings composite material loaded with nano zero-valent metals. In principle, the amorphization treatment can effectively destroy the chain structure of silicate minerals in the tailings, promote the release of a large number of silicon atoms, disintegrate the tailings crystal structure, and form a multi-porous structure on the surface. This process effectively increases the specific surface area of the tailings and its adsorption capacity for cadmium ions. Further, in order to improve the adsorption performance of amorphous tailings for arsenic, nano zero-valent metals are introduced on its surface. Since the amorphous tailings have a larger specific surface area, compared with the original tailings, the nano zero-valent metal achieves a better dispersion effect on its surface and can be more effectively utilized, so the composite material finally prepared can adsorb cadmium and arsenic at the same time. The amorphous tailings composite material loaded with nano-zero-valent metals prepared by this method has high-efficiency adsorption performance and good magnetic recovery characteristics, and the entire preparation process is simple and easy and can be mass-produced.
[0007] Another object of the present invention is to provide an amorphous tailings-based cadmium and arsenic simultaneous adsorption material prepared by the above preparation method.
[0008] Another object of the present invention is to provide the use of the above-mentioned amorphous tailings-based cadmium and arsenic simultaneous adsorption material in adsorbing cadmium and arsenic in water or soil.
[0009] During the application process, the amorphous tailings composite material loaded with nano zero-valent metals can effectively adsorb cadmium and arsenic in water and soil environments at the same time. Since the composite material has strong magnetism, after the adsorption process is completed, the material can be easily recovered from the water or soil by applying an external magnetic field, thereby minimizing the risk of secondary pollution.
[0010] The purpose of the present invention is achieved through the following technical solutions:
[0011] A method for preparing an amorphous tailings-based cadmium-arsenic simultaneous adsorption material comprises the following steps:
[0012] (1) mixing the tailings with alkali or alkaline salt, calcining, washing, and drying to obtain an amorphous tailings solid product;
[0013] (2) The amorphous tailings solid product is ground and sieved, and then added to a metal ion solution and mixed. Then, a reducing agent is added dropwise to generate nano-zero-valent metal on the surface of the amorphous tailings. After the addition is completed, the reaction is continued for a period of time to ensure the generation of a uniform and stable composite material, and then washed and dried to obtain an amorphous tailings composite material loaded with nano-zero-valent metal.
[0014] Preferably, the tailings in step (1) are at least one of molybdenum tailings, iron tailings, copper tailings and gold tailings.
[0015] Preferably, the tailings in step (1) need to pass through a 50-200 mesh sieve.
[0016] Preferably, the alkali or alkaline salt in step (1) is at least one of NaOH, Na2CO3, KOH, K2CO3, Ca(OH)2 and CaCO3.
[0017] Preferably, the mass ratio of the alkali or alkaline salt to the tailings in step (1) is (1-5):(0.5-2); more preferably 2:1.
[0018] Preferably, the calcination temperature in step (1) is 300-1000°C; more preferably 600°C.
[0019] Preferably, the calcination time in step (1) is 2 to 8 hours; more preferably 4 hours.
[0020] Preferably, the calcined product in step (1) is washed by alternating washing with 0.01-0.1 mol / L hydrochloric acid solution and deionized water until the pH value of the solution after washing is neutral; more preferably, the concentration of the hydrochloric acid solution is 0.05 mol / L.
[0021] Preferably, the drying method in step (1) is to place the mixture in an oven for drying at a temperature of 40 to 120° C. for a drying time of 6 to 24 hours.
[0022] Preferably, the amorphous tailings solid product in step (2) needs to pass through a 50-150 mesh sieve.
[0023] Preferably, the metal ion in the metal ion solution in step (2) is Fe 2+ , Fe 3+ and Mn 2+ At least one of Fe 2+ ; The metal ion solution is at least one of FeSO4 solution, Fe2(SO4)3 solution, FeCl2 solution, FeCl3 solution, MnSO4 solution and MnCl2 solution, and is more preferably FeSO4 solution; the mass ratio of metal salt to water in the metal ion solution is (1-10):(100-500), more preferably (1-2):100; more preferably 1.3:100.
[0024] Preferably, the mass ratio of the metal salt in the metal ion solution of step (2) to the amorphous tailings solid product is (1-10):(1-100); more preferably (1-2):1; most preferably 1.3:1.
[0025] Preferably, in step (2), the amorphous tailings solid product and the metal ion solution are mixed by ultrasound and stirring, the ultrasound time is 20 to 60 minutes; the stirring time is 1 to 8 hours, and the stirring rate is 100 to 500 r / min.
[0026] Preferably, the reducing agent in step (2) is sodium borohydride (NaBH4); the reducing agent is added dropwise in the form of a reducing agent solution, wherein the mass ratio of the reducing agent to water is (1-5):(1-500); more preferably (1-3):100; and most preferably 1.9:100.
[0027] Preferably, in step (2), the molar ratio of the reducing agent to the metal ion is 200:(5-50).
[0028] Preferably, the reducing agent droplet acceleration rate in step (2) is 50 to 150 drops / min; more preferably 60 drops / min.
[0029] Preferably, after the reducing agent is added dropwise in step (2), the stirring reaction is continued for 0.5 to 5 hours; more preferably for 2 hours.
[0030] Preferably, the washing in step (2) is washing with water, and the drying is conventional freeze-drying in the art.
[0031] The above preparation method obtains an amorphous tailings-based cadmium and arsenic simultaneous adsorption material.
[0032] The above-mentioned amorphous tailings-based cadmium and arsenic simultaneous adsorption material is used to adsorb cadmium and arsenic in water or soil.
[0033] Preferably, the soil is paddy field soil, and the amorphous tailings-based cadmium and arsenic simultaneous adsorption material is applied at 0.025-0.5% of the water mass or 0.5-3% of the soil mass.
[0034] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0035] (1) The present invention provides a method for resource recycling of tailings solid waste. The inherent crystal structure of the tailings is destroyed by alkali treatment under high temperature conditions, thereby obtaining amorphous tailings. The amorphous tailings have a large specific surface area and a high reaction activity, and exhibit a good adsorption effect on cadmium. In addition, the amorphous tailings also provide an ideal carrier for the loading of nano zero-valent metals, so that the nano zero-valent metals can achieve a better dispersion effect, so the obtained nano zero-valent metal loaded amorphous tailings composite material has a good adsorption effect on cadmium and arsenic.
[0036] (2) The composite material of the present invention has simple preparation steps and low cost, and has certain industrialization potential. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 1 is the XRD spectrum of the MoT material in Comparative Example 1 and the AMoT material in Example 1.
[0038] Figure 2 (a) and (b) are the HR-TEM images and SAED images of the AMoT material in Example 1.
[0039] Figure 3 This is the XRD pattern of the nZVI@AMoT material in Example 2.
[0040] Figure 4 SEM images of the MoT material (a) in comparative example 1, the AMoT material (b) in example 1, the nZVI@MoT material (c) in comparative example 2, and the nZVI@AMoT material (d) in example 2.
[0041] Figure 5 The removal rates of cadmium in the unitary system by the AMoT material in Example 1, the MoT material in Comparative Example 1, the nZVI@AMoT material in Example 2, and the nZVI@MoT material in Comparative Example 2 are shown.
[0042] Figure 6 The removal rates of arsenic in the unitary system by the AMoT material in Example 1, the MoT material in Comparative Example 1, the nZVI@AMoT material in Example 2, and the nZVI@MoT material in Comparative Example 2 are shown.
[0043] Figure 7 The removal rates of cadmium and arsenic in the binary system by the AMoT material in Example 1, the MoT material in Comparative Example 1, the nZVI@AMoT material in Example 2, and the nZVI@MoT material in Comparative Example 2.
[0044] Figure 8 The passivation rates of the AMoT material in Example 1, the MoT material in Comparative Example 1, the nZVI@AMoT material in Example 2, and the nZVI@MoT material in Comparative Example 2 for cadmium and arsenic in contaminated soil. DETAILED DESCRIPTION
[0045] The present invention is further described in detail below in conjunction with examples and drawings, but the embodiments of the present invention are not limited thereto.
[0046] If no specific conditions are specified in the examples of the present invention, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. All raw materials, reagents, etc., whose manufacturers are not specified, are conventional products that can be purchased commercially.
[0047] Example 1
[0048] Preparation of amorphous tailings:
[0049] 1.1 Preparation of amorphous molybdenum tailings (AMoT)
[0050] Molybdenum tailings (SiO2 78.35%, Al2O3 10.95%, CaO 0.64%, MgO 0.42%, Fe2O3 1.54%, the remainder is impurities) taken from the tailings pond of Baishizhang Molybdenum Tungsten Mine in Wuhua County, Meizhou City, Guangdong Province, were mixed with NaOH particles in a mass ratio of 1:2 and then placed in a muffle furnace for calcination at 600℃ for 4 hours. The calcined product was taken out and washed alternately with 0.05mol / L hydrochloric acid solution and deionized water until the material was neutral. After drying at 80℃, it was ground and passed through a 60-mesh sieve. The obtained material was amorphous molybdenum tailings (AMoT).
[0051] 1.2 Preparation of amorphous iron tailings (AFeT)
[0052] The iron tailings (SiO2 55.65%, Al2O3 15.25%, CaO 5.21%, MgO 3.10%, Fe2O3 10.04%, the remainder is impurities) from the tailings pond of Xishimen Iron Mine Area, Wu'an City, Hebei Province were mixed with NaOH particles in a mass ratio of 1:2 and calcined in a muffle furnace at 600°C for 4 hours. The calcined product was taken out and washed alternately with 0.05mol / L hydrochloric acid solution and deionized water until the material was neutral. After drying at 80°C, it was ground and passed through a 60-mesh sieve. The obtained material was amorphous iron tailings (AFeT).
[0053] 1.3 Preparation of amorphous copper tailings (ACuT)
[0054] Copper tailings (SiO2 65.23%, Al2O3 12.49%, CaO 3.01%, MgO 3.28%, Fe2O3 5.13%, the remainder is impurities) taken from the tailings pond of Laoyaling Mine in Tongling City, Anhui Province were mixed with NaOH particles in a mass ratio of 1:2 and calcined in a muffle furnace at 600℃ for 4 hours. The calcined product was taken out and washed alternately with 0.05mol / L hydrochloric acid solution and deionized water until the material was neutral. After drying at 80℃, it was ground and passed through a 60-mesh sieve. The obtained material was amorphous copper tailings (ACuT).
[0055] 1.4 Preparation of amorphous gold tailings (AAuT)
[0056] Gold tailings (SiO2 75.21%, Al2O3 6.35%, CaO 3.51%, MgO 1.54%, Fe2O3 5.13%, the remainder is impurities) taken from the Xiling gold mine tailings pond in Laizhou City, Yantai City, Shandong Province were mixed with NaOH particles in a mass ratio of 1:2 and calcined in a muffle furnace at 600°C for 4 hours. The calcined product was taken out and washed alternately with 0.05mol / L hydrochloric acid solution and deionized water until the material was neutral. After drying at 80°C, it was ground and passed through a 60-mesh sieve. The obtained material was amorphous gold tailings (AAuT).
[0057] Example 2
[0058] 2.1 Preparation of nano-zero-valent iron-loaded amorphous molybdenum tailings composites (nZVI@AMoT)
[0059] At room temperature, 1.28g of ferrous sulfate powder was added to a beaker containing 100mL of deionized water, stirred until completely dissolved, and then 0.96g of AMoT was added. After ultrasonication for 30 minutes, it was transferred to a 500mL three-necked flask. The suspension in the three-necked flask was mechanically stirred at a speed of 200r / min for 2h. 1.90g of NaBH4 was dissolved in 100mL of water to prepare a NaBH4 solution, and the NaBH4 solution was added to the flask at a drop rate of 60 drops / min. After the addition was completed, the reaction was continued for 2 hours to ensure the formation of a uniform and stable composite material. After the reaction was completed, the mixture was poured into a beaker, and the composite material was recovered from the solution by an external magnetic field and washed three times with deionized water. Finally, the composite material was placed in a vacuum dryer at -50°C to obtain an amorphous molybdenum tailings material (nZVI@AMoT) loaded with nano zero-valent iron.
[0060] 2.2 Preparation of nano-zero-valent iron loaded amorphous iron tailings composites (nZVI@AFeT)
[0061] At room temperature, 1.28g of ferrous sulfate powder was added to a beaker containing 100mL of deionized water, stirred until completely dissolved, and then 0.96g of AFeT was added. After ultrasonication for 30 minutes, the mixture was transferred to a 500mL three-necked flask. The suspension in the three-necked flask was mechanically stirred at 200r / min for 2h. 1.90g of NaBH4 was dissolved in 100mL of water to prepare a NaBH4 solution, and the NaBH4 solution was added to the flask at a drop rate of 60 drops / min. After the addition was completed, the reaction was continued for 2 hours to ensure the formation of a uniform and stable composite material. After the reaction was completed, the mixture was poured into a beaker, the composite material was recovered from the solution by an external magnetic field, and washed three times with deionized water. Finally, the composite material was vacuum dried at -50°C to obtain an amorphous iron tailings material loaded with nano-zero-valent iron (nZVI@AFeT)
[0062] 2.3 Preparation of nano-zero-valent iron-loaded amorphous copper tailings composites (nZVI@ACuT)
[0063] At room temperature, 1.28g of ferrous sulfate powder was added to a beaker containing 100mL of deionized water, stirred until completely dissolved, and then 0.96g of ACuT was added. After ultrasonication for 30 minutes, it was transferred to a 500mL three-necked flask. The suspension in the three-necked flask was mechanically stirred at a speed of 200r / min for 2h. 1.90g of NaBH4 was dissolved in 100mL of water to prepare a NaBH4 solution, and the NaBH4 solution was added to the flask at a drop rate of 60 drops / min. After the addition was completed, the reaction was continued for 2 hours to ensure the formation of a uniform and stable composite material. After the reaction was completed, the mixture was poured into a beaker, and the composite material was recovered from the solution by an external magnetic field and washed three times with deionized water. Finally, the composite material was placed in a vacuum dryer at -50°C to obtain an amorphous copper tailings material (nZVI@ACuT) loaded with nano zero-valent manganese.
[0064] 2.4 Preparation of nanometer zero-valent iron loaded amorphous gold tailings composites (nZVI@AAuT)
[0065] At room temperature, 1.28g of ferrous sulfate powder was added to a beaker containing 100mL of deionized water, stirred until completely dissolved, and then 0.96g of AAuT was added. After ultrasonication for 30 minutes, the mixture was transferred to a 500mL three-necked flask. The suspension in the three-necked flask was mechanically stirred at 200r / min for 2h. 1.90g of NaBH4 was dissolved in 100mL of water to prepare a NaBH4 solution, and the NaBH4 solution was added to the flask at a drop rate of 60 drops / min. After the addition was completed, the reaction was continued for 2 hours to ensure the formation of a uniform and stable composite material. After the reaction was completed, the mixture was poured into a beaker, the composite material was recovered from the solution by an external magnetic field, and washed three times with deionized water. Finally, the composite material was vacuum dried at -50°C to obtain an amorphous gold tailings material (nZVI@AAuT) loaded with nano-zero-valent nickel.
[0066] Example 3
[0067] At room temperature, 1.28g of ferric sulfate powder was added to a beaker containing 100mL of deionized water, stirred until completely dissolved, and then 0.96g of AMoT was added. After ultrasonication for 30 minutes, it was transferred to a 500mL three-necked flask. The suspension in the three-necked flask was mechanically stirred at a speed of 200r / min for 2h. 1.90g of NaBH4 was dissolved in 100mL of water to prepare a NaBH4 solution, and the NaBH4 solution was added to the flask at a drop rate of 60 drops / min. After the addition was completed, the reaction was continued for 2 hours to ensure the formation of a uniform and stable composite material. After the reaction was completed, the mixture was poured into a beaker, and the composite material was recovered from the solution by an external magnetic field and washed three times with deionized water. Finally, the composite material was placed in a vacuum dryer at -50°C to obtain an amorphous molybdenum tailings material (nZVI@AMoT-1) loaded with nano zero-valent iron.
[0068] Example 4
[0069] At room temperature, 1.28g of manganese sulfate powder was added to a beaker containing 100mL of deionized water, stirred until completely dissolved, and then 0.96g of AMoT was added. After ultrasonication for 30 minutes, it was transferred to a 500mL three-necked flask. The suspension in the three-necked flask was mechanically stirred at a speed of 200r / min for 2h. 1.90g of NaBH4 was dissolved in 100mL of water to prepare a NaBH4 solution, and the NaBH4 solution was added to the flask at a drop rate of 60 drops / min. After the addition was completed, the reaction was continued for 2 hours to ensure the formation of a uniform and stable composite material. After the reaction was completed, the mixture was poured into a beaker, and the composite material was recovered from the solution by an external magnetic field and washed three times with deionized water. Finally, the composite material was placed in a vacuum dryer at -50°C to obtain an amorphous molybdenum tailings material (nano-Mn@AMoT) loaded with nano-zero-valent manganese.
[0070] Comparative Example 1
[0071] 1.1 A molybdenum tailings material (MoT), which is different from Example 1.1 in that the molybdenum tailings have not been subjected to high-temperature calcination treatment and still retain a complete crystal structure.
[0072] 1.2 An iron tailings material (FeT), which is different from Example 1.2 in that the iron tailings has not been subjected to high-temperature calcination treatment and still retains a complete crystal structure.
[0073] 1.3 A copper tailings material (CuT), which is different from Example 1.3 in that the copper tailings have not been subjected to high-temperature calcination treatment and still retain a complete crystal structure.
[0074] 1.4 A gold tailings material (AuT), which is different from Example 1.3 in that the gold tailings have not been subjected to high-temperature calcination treatment and still retain a complete crystal structure.
[0075] Comparative Example 2
[0076] 2.1 A composite material of molybdenum tailings loaded with nano zero-valent iron (nZVI@MoT), which is different from Example 2.1 in that the molybdenum tailings have not been subjected to high-temperature calcination treatment and still retain a complete crystal structure.
[0077] 2.2 A composite material of iron tailings loaded with nano zero-valent iron (nZVI@FeT), which is different from Example 2.2 in that the iron tailings have not been subjected to high-temperature calcination treatment and still retains a complete crystal structure.
[0078] 2.3 A composite material of copper tailings loaded with nano zero-valent iron (nZVI@CuT), which is different from Example 2.3 in that the copper tailings has not been subjected to high-temperature calcination treatment and still retains a complete crystal structure.
[0079] 2.4 A composite material of gold tailings loaded with nano zero-valent iron (nZVI@AuT), which is different from Example 2.4 in that the gold tailings have not been subjected to high-temperature calcination treatment and still retains a complete crystal structure.
[0080] Comparative Example 3
[0081] A composite material of molybdenum tailings loaded with nano zero-valent iron (nZVI@MoT-1), which differs from Example 3 in that the molybdenum tailings has not been subjected to high-temperature calcination treatment and still retains a complete crystal structure.
[0082] Comparative Example 4
[0083] A composite material of molybdenum tailings loaded with nano zero-valent iron (nano-Mn@MoT), which is different from Example 4 in that the molybdenum tailings have not been subjected to high-temperature calcination treatment and still retain a complete crystal structure.
[0084] Figure 1 The XRD spectra of the MoT material in Comparative Example 1 and the AMoT material in Example 1 are shown in Figure 1. As can be seen from the figure, MoT shows a high degree of crystallinity and has characteristic peaks of quartz, illite and phlogopite. However, the XRD spectrum of AMoT has no obvious characteristic peaks and presents a broad amorphous peak in the range of 19.35° to 37.60°, indicating that the ordered crystal structure of the mineral in MoT has been destroyed.
[0085] Figure 2 The HR-TEM image (a) and SAED image (b) of the AMoT material prepared in Example 1 of the present invention are shown in FIG. As can be seen from the figure, the AMoT lattice is disordered and has no obvious stripes ( Figure 2 In addition, the weak rings observed in SAED also indicate that AMoT has poor crystallinity ( Figure 2 These findings further confirmed the amorphous structure of AMoT.
[0086] Figure 3 The XRD pattern of the nZVI@AMoT material prepared in Example 2 of the present invention. The sharp peak at 44.82° confirms the successful preparation of nZVI and its effective loading on AMoT (PDF#06-0696). At the same time, due to the oxidation characteristics of nZVI, characteristic peaks attributed to Fe2O3 (2θ=31.28°, 62.51°) and FeOOH (2θ=21.11°) were also observed.
[0087] Figure 4 The SEM images of the MoT material, AMoT material, nZVI@MoT material and nZVI@AMoT material prepared in the present invention. Among them, (a) is the SEM image of the MoT material in comparative example 1 of the present invention, (b) is the SEM image of the AMoT material in Example 1 of the present invention, (c) is the SEM image of the nZVI@MoT material in comparative example 2 of the present invention, and (d) is the SEM image of the nZVI@AMoT material in Example 2 of the present invention. It can be seen from the figure that the surface morphology of MoT is a relatively smooth block structure without obvious pore characteristics. After high-temperature calcination treatment, the surface of AMoT is transformed into a relatively rough morphology, accompanied by the formation of a multi-channel structure. This transformation effectively improves the pore volume and specific surface area of AMoT, while enhancing the adsorption performance, it also creates favorable conditions for the uniform dispersion of nZVI. Figure 1 Figure c shows that when MoT is used as a carrier to load nZVI, nZVI is not well dispersed. However, when AMoT is used as a carrier to load nZVI, spherical nanoparticles with similar particle sizes are evenly dispersed on the surface of AMoT, proving that AMoT can effectively solve the agglomeration problem of nano-zero-valent iron by using its unique mineral three-dimensional architecture and lattice changes.
[0088] Example 5
[0089] Application example of nano-zero-valent metal-loaded amorphous tailings composite material adsorbing cadmium in water
[0090] Weigh 25 mg of the AMoT material prepared in Example 1, the nZVI@AMoT composite material prepared in Example 2, the MoT obtained in Comparative Example 1, and the nZVI@MoT material obtained in Comparative Example 2 into a 50 mL centrifuge tube, and add 50 mL of a 100 ppm Cd(II) solution (prepared with 0.274 g Cd(NO3)2·4H2O crystals and 1000 mL 0.01 mol / L NaNO3) into the centrifuge tube. Oscillate at a constant speed of 180 r / min at 25°C, take out after adsorption for 24 hours, take 5 mL of the solution and filter it through a 0.45 μm acetate fiber filter head, and determine the cadmium content in the filtrate by atomic absorption spectrophotometry. The removal rate of cadmium ions in the adsorption solution is as follows: Figure 5 shown.
[0091] Example 6
[0092] Application example of adsorption of arsenic in water by nano-zero-valent metal-loaded amorphous tailings composite materials
[0093] Weigh 25 mg of the AMoT material prepared in Example 1, the nZVI@AMoT composite material prepared in Example 2, the MoT obtained in Comparative Example 1, and the nZVI@MoT material obtained in Comparative Example 2 into a 50 mL centrifuge tube, and add 50 mL of a 100 ppm As(III) solution (composed of 0.173 g NaAsO2 crystals and 1000 mL 0.01 mol / L NaNO3) into the centrifuge tube. Oscillate at a constant speed of 180 r / min at 25°C, take out after adsorption for 24 hours, take 5 mL of the solution and filter it through a 0.45 μm acetate fiber filter head, and determine the arsenic content in the filtrate by atomic fluorescence spectrometry. The removal rate of arsenic ions in the adsorption liquid is as follows: Figure 6 shown.
[0094] Example 7
[0095] Application example of simultaneous adsorption of cadmium and arsenic in water by nano-zero-valent metal-loaded amorphous tailings composite materials
[0096] Weigh 25 mg of the AMoT material prepared in Example 1, the nZVI@AMoT composite material prepared in Example 2, the MoT obtained in Comparative Example 1, and the nZVI@MoT material obtained in Comparative Example 2 into a 50 ml centrifuge tube, and add 50 ml of an As-Cd composite solution (composed of 0.173 g of NaAsO2 crystals, 0.274 g of Cd(NO3)2·4H2O crystals and 1000 mL of 0.01 mol / L NaNO3) with As(Ⅲ) and Cd(Ⅱ) concentrations of 100 ppm to the centrifuge tube. Oscillate at a constant speed of 180 r / min at 25°C, take out after adsorption for 24 hours, take 5 ml of the solution and filter it through a 0.45 μm acetate fiber filter head, and determine the arsenic and cadmium contents in the filtrate by atomic fluorescence spectroscopy and atomic absorption spectrophotometry. The removal rate of cadmium and arsenic ions in the adsorption solution is as follows: Figure 7 shown.
[0097] Example 8
[0098] Weigh 100g of cadmium-arsenic composite contaminated soil, with soil cadmium and arsenic concentrations of 2.89 and 42.1mg / kg respectively, maintain 70% of the maximum field water holding capacity of the soil, add 2% of the soil mass to the composite material prepared in Example 2 and Comparative Example 2, and incubate at a constant temperature of 25±2°C for 30 days. The soil sample was then air-dried, ground, and sieved through a 100-mesh sieve for later use. The effective cadmium content of the soil was extracted with CaCl2 solution, and the effective arsenic content of the soil was extracted with NH4H2PO4 solution. The contents of arsenic and cadmium in the extract were determined by atomic fluorescence spectroscopy and atomic absorption spectrophotometry. The experimental results of soil cadmium and arsenic passivation rate are shown in the figure. Figure 8 shown.
[0099] Table 1 The test of the maximum adsorption amount of cadmium and arsenic in water is based on Example 7, where the constant temperature incubation time at 25°C is 24h. The test of the passivation effect of cadmium and arsenic in soil is based on Example 8, where the constant temperature incubation time at 25±2°C is 30d.
[0100] Table 1 The repair effects of various embodiments and comparative examples on cadmium and arsenic in the composite pollution system
[0101]
[0102]
[0103] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A method for preparing an amorphous tailings-based cadmium and arsenic simultaneous adsorption material, characterized in that: The following steps are involved: (1) mixing the tailings with alkali or alkaline salt, calcining, washing, and drying to obtain an amorphous tailings solid product; (2) The amorphous tailings solid product is ground and sieved, and then added to the metal ion solution and mixed, and then a reducing agent is added dropwise and the reaction is continued for a period of time, washed, and dried to obtain an amorphous tailings composite material loaded with nano-zero-valent metals.
2. The method for preparing an amorphous tailings-based cadmium and arsenic simultaneous adsorption material according to claim 1, characterized in that: The tailings in step (1) are at least one of molybdenum tailings, iron tailings, copper tailings and gold tailings; The alkali or alkaline salt in step (1) is at least one of NaOH, Na2CO3, KOH, K2CO3, Ca(OH)2 and CaCO3; The mass ratio of the alkali or alkaline salt to the tailings in step (1) is (1-5): (0.5-2).
3. The method for preparing an amorphous tailings-based cadmium and arsenic simultaneous adsorption material according to claim 1 or 2, characterized in that: The calcination temperature in step (1) is 300 to 1000° C. and the calcination time is 2 to 8 hours.
4. The method for preparing an amorphous tailings-based cadmium and arsenic simultaneous adsorption material according to claim 3, characterized in that: The metal ion in the metal ion solution of step (2) is Fe 2+ , Fe 3+ and Mn 2+ At least one of; The mass ratio of the metal salt in the metal ion solution and the amorphous tailings solid product in step (2) is (1-10): (1-100); The molar ratio of the reducing agent to the metal ion in step (2) is 200:(5-50).
5. The method for preparing an amorphous tailings-based cadmium and arsenic simultaneous adsorption material according to claim 3, characterized in that: The reducing agent in step (2) is sodium borohydride; the reducing agent is added dropwise in the form of a reducing agent solution, wherein the mass ratio of the reducing agent to water is (1-5): (1-500); The reducing agent drop acceleration rate in step (2) is 50 to 150 drops / min; After the reducing agent in step (2) is added dropwise, the reaction is continued with stirring for 0.5 to 5 hours.
6. The method for preparing an amorphous tailings-based cadmium and arsenic simultaneous adsorption material according to claim 3, characterized in that: The metal ion solution is at least one of FeSO4 solution, Fe2(SO4)3 solution, FeCl2 solution, FeCl3 solution, MnSO4 solution and MnCl2 solution; The mass ratio of the metal salt to water in the metal ion solution is (1-10):(100-500).
7. The method for preparing an amorphous tailings-based cadmium and arsenic simultaneous adsorption material according to claim 3, characterized in that: The tailings in step (1) need to be sieved through a 50-200 mesh screen; The calcined product is washed in step (1) by alternately washing with 0.01-0.1 mol / L hydrochloric acid solution and deionized water until the pH value of the solution after washing is neutral; The drying temperature in step (1) is 40 to 120° C. and the drying time is 6 to 24 hours; The amorphous tailings solid product in step (2) needs to pass through a 50-150 mesh sieve; In step (2), the amorphous tailings solid product and the metal ion solution are mixed by ultrasound and stirring, wherein the ultrasound time is 20 to 60 minutes; the stirring time is 1 to 8 hours, and the stirring rate is 100 to 500 r / min.
8. An amorphous tailings-based cadmium and arsenic simultaneous adsorption material prepared by the preparation method according to any one of claims 1 to 7.
9. Use of the amorphous tailings-based cadmium and arsenic simultaneous adsorption material according to claim 8 in adsorbing cadmium and arsenic in water or soil.
10. The use according to claim 9, characterized in that: The amorphous tailings-based cadmium and arsenic simultaneous adsorption material is applied at 0.025-0.5% of the mass of the water body or 0.5-3% of the mass of the soil.